2006
DOI: 10.1159/000094742
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Inapparent Adrenal Mass in a Patient with Familial Adenomatous Polyposis

Abstract: Familial adenomatous polyposis (FAP) is an autosomal dominant condition characterized by multiple colorectal adenomas that can progress to carcinoma. FAP can be associated with diverse extracolonic manifestation, including desmoid tumors and adrenal masses. We report our experience with a patient diagnosed of FAP, who developed a desmoid tumor and an adrenal mass in the follow-up. To our knowledge, this is the first case in the literature in which a hypersecretion of aldosterone and cortisol in the adrenal mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“… 69 , 74 Most adrenal adenomas do not produce hormones, although production of cortisol, 66 , 69 , 76 aldosterone 65 and their combination have been reported. 73 Smith et al. described a patient with a pheochromocytoma.…”
Section: Fap and Adrenal Tumorsmentioning
confidence: 99%
“… 69 , 74 Most adrenal adenomas do not produce hormones, although production of cortisol, 66 , 69 , 76 aldosterone 65 and their combination have been reported. 73 Smith et al. described a patient with a pheochromocytoma.…”
Section: Fap and Adrenal Tumorsmentioning
confidence: 99%
“…FAP-associated adrenal tumors can produce mineralocorticoids, 10 corticosteroids, 5 or both. 11 In addition, there are reports of FAP patients developing pheochromocytoma 2 and adrenocortical carcinoma. 5 In a mortality study that investigated the causes of death in 132 FAP patients, one patient was found to have died of adrenal cancer.…”
mentioning
confidence: 99%